Perceptions of Distributive Justice in Latin America during a Period of Falling Inequality - Reyes, German; Gasparini, Leonardo (World Bank, Washington, DC, 2017)
This paper explores perceptions of distributive justice in Latin America during the 2000s and their relationship with income inequality. In line with the fall in income inequality in the region, the paper documents a widespread, although modest, decrease in the share of the population that believes income distribution is unfair. The fall in the perception of unfairness holds across very heterogeneous groups of the population. Moreover, perceptions evolved in the same direction as income inequality for 17 of the 18 countries for which microdata are available. The analysis reveals that unfairness perceptions are more correlated with relative measures of income inequality than absolute ones, and that individual characteristics are correlated with distributive perceptions. On average, individuals who are older, more educated, unemployed, and left-wing tend to perceive income distribution as more unfair. The paper shows that the decrease in unfairness perceptions during the past decade was due to changes in inequality, rather than to composition effects. Finally, the paper shows that individuals who perceive income distribution as very unfair are more prone to mobilize and protest.